2018
DOI: 10.1016/j.envres.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

A nested case-control study of polychlorinated biphenyls, organochlorine pesticides, and thyroid cancer in the Janus Serum Bank cohort

Abstract: Emissions of PCBs and OC pesticides varied over time. Different risk patterns by birth cohort suggest the potential importance of timing of exposure in thyroid cancer risk. Further evaluation of these associations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…Heterogeneous results were found among selected studies when the association between pesticide exposure and HNC cancer was evaluated. Some studies did not found evidence of any association between pesticides exposure and HNC ( 16 , 19 , 21 , 22 , 26 ). On the other hand, most of them found a positive association between pesticide exposure with cancer in larynx ( 2 , 20 , 25 ), pharynx ( 17 ), nasal cavity and nasopharynx ( 18 ), and sinonasal areas ( 22 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneous results were found among selected studies when the association between pesticide exposure and HNC cancer was evaluated. Some studies did not found evidence of any association between pesticides exposure and HNC ( 16 , 19 , 21 , 22 , 26 ). On the other hand, most of them found a positive association between pesticide exposure with cancer in larynx ( 2 , 20 , 25 ), pharynx ( 17 ), nasal cavity and nasopharynx ( 18 ), and sinonasal areas ( 22 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to SIGN 50 criteria, 6 selected studies received an overall high-quality ( 2 , 17 , 18 , 20 , 24 , 25 ), 2 studies were considered with accepTable quality ( 22 , 23 ), and 4 studies were classified with a modest quality ( 16 , 19 , 21 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After stratification by gender, they found a significant positive association between PCB-118 exposure and the risk of thyroid cancer in the 2nd (serum concentration of 2.43–4.10 ng/g) vs. 1st quartile in females (OR: 1.90; 95% CI: 1.10–3.27) and males (OR: 1.96; 95% CI: 1.16–3.33) [ 54 ]. In a nested case-control study by Lerro et al (2018) PCBs were not associated with thyroid cancer with the exception of congener PCB-114 which was present at low concentrations and inversely associated with thyroid cancer (OR per 1 ng/g increase: 0.78; 95% CI: 0.62–0.97) [ 55 ]. The same study found a positive association between total PCB exposure (OR: 1.25; 95% CI: 1.00–1.56), PCB 138/158 (OR: 4.54; 95% CI: 1.20–17.2) and PCB 153 (OR: 3.47; 95% CI: 1.18–10.2) with thyroid cancer but only among individuals in the youngest birth cohort (individuals born between 1943–1957) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a nested case-control study by Lerro et al (2018) PCBs were not associated with thyroid cancer with the exception of congener PCB-114 which was present at low concentrations and inversely associated with thyroid cancer (OR per 1 ng/g increase: 0.78; 95% CI: 0.62–0.97) [ 55 ]. The same study found a positive association between total PCB exposure (OR: 1.25; 95% CI: 1.00–1.56), PCB 138/158 (OR: 4.54; 95% CI: 1.20–17.2) and PCB 153 (OR: 3.47; 95% CI: 1.18–10.2) with thyroid cancer but only among individuals in the youngest birth cohort (individuals born between 1943–1957) [ 55 ]. Similarly, Deziel et al (2020) found no significant association between PCBs and PTC among 250 female incident cases and 250 controls in Connecticut.…”
Section: Resultsmentioning
confidence: 99%